A Portable Distance Learning Approach for Image Processing Course in FKEE, UTHM - Haw, Jia Hui; Sari, Suhaila; Roslan, Hazli; Md Taujuddin, Nik Shahidah Afifi; Ibrahim, Nabilah (Evolution in Electrical and Electronic Engineering, 2022)
This study discusses a portable distance learning method for the Image Processing course in FKEE, UTHM. The traditional teaching method mainly focuses on the theories with the lack of visual demonstration. It has been difficult to imagine the actual output image through only the theories and equations in notes. In this study, an Android-based Image Processing learning application is developed using Android Studio software. The Open CV (Open Source Computer Vision) library is added to the Android Studio as a library of programming functions for real-time image processing. This application provides the complete theoretical chapters based on the image processing course syllabus as well as the real-time processing functions. There are 10 sample images provided for users to perform image processing. Then, the users can apply the desired image processing techniques provided to the selected image depending on their needs. The survey is conducted to analyze the performance of applications. In conclusion, the Image Processing application has been successfully developed. This proposed Android application is believed to assist students in better understanding of image processing.